Micro-Teaching Strategy for Effective Yellow Book Learning in Formal Educational Environments - Muhammad Rizaludin; Euis Latipah; Muhammad Yusu Rivaldi; Sahlal Ma`ruf Basyir (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
Learning the yellow book is an integral part of the Islamic educational tradition in Indonesia. However, integrating this learning method into formal educational environments presents its own challenges. This paper aims to describe the micro-teaching strategy as a practical and innovative approach to increasing the effectiveness of yellow book learning. This article uses a qualitative-descriptive approach with a literature review and observations of the PPL 1 practice. The results indicate that through micro-teaching, students are able to practice teaching skills systematically and reflectively, and are able to structure and implement yellow book learning in a contextual, active, and enjoyable manner. The addition of educational technology and authentic evaluation also helps strengthen students' understanding of classical Arabic texts.